ILMUWAN BAHASA DAN SASTRA, SERTA KENDALAKENDALANYA - I Dewa Putu Wijana (Seminar Bahasa dan Sastra Indonesia, 2019)
Language and literature do not just constitute one of the most interesting subject matters to study, they also conceal a lot of glorious values owned by the speech communities. To enable revealing the cultural noble values hidden in Indonesian, the local languages, as well as in their literary works, the language and literary researchers should be equiped themselves with an adequate linguistic and literary theories inspite of fully mastering the language of the verbal works use to convey. However, as far as Indonesian condition is concerned, linguists and literary experts are faced with a lot of obstacles in order to produce serious and profound studies in their field. Some of the constraints among many others are lack of motivation, time and financial shortages, low English or foreign language profeciency, approprieteness of languages and literary works that should become the study objects, and the negative impacts of modern technology. Keyword:Linguists, literary critics, constraints